2022
DOI: 10.3390/microorganisms10102055
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Indoor Air Quality of Four Primary Health Care Centers in Qatar

Abstract: Airborne bacteria pose a potential risk to human health upon inhalation in the indoor environments of health care facilities. Airborne bacteria may originate from various sources, including patients, workers, and daily visitors. Hence, this study investigates the quantity, size, and identification of airborne bacteria indoors and outdoors of four Primary Health Care Centers (PHCC) in Doha, Qatar. Air samples were collected from the lobby, triage room, and outside environment of the centers, including, Qatar Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Droplets containing these microorganisms survive in favorable conditions such as dry and cool atmospheres without direct exposure to sunlight. Indoor air quality in hospitals is very important because many related studies have statistically revealed and measured airborne microorganisms that can potentially cause HAIs (16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…Droplets containing these microorganisms survive in favorable conditions such as dry and cool atmospheres without direct exposure to sunlight. Indoor air quality in hospitals is very important because many related studies have statistically revealed and measured airborne microorganisms that can potentially cause HAIs (16)(17).…”
Section: Discussionmentioning
confidence: 99%